Adaptive livelihood strategies employed by farmers to close the food gap in semi-arid south eastern Zimbabwe - Murungweni, C.; Wijk, Mark T. van; Giller, Kenneth E.; Andersson, Jens A.; Smaling, E.M.A. (Springer, 2014)
Rural households in semi-arid areas of southern Africa are confronted with numerous hazards that threaten the household food base. The new wildlife policy of establishing transfrontier conservation areas aims to increase conservation of wildlife resources while improving local livelihoods. This policy can be better appreciated by local people if it embraces knowledge of the adaptive strategies they employ to close the food gap. We assessed how different households responded to the major hazard, drought, in order to gain insight into how these households addressed critical questions of food availability. Informal interviews, key informant interviews and focus group discussions were conducted to determine how households can be disaggregated according to their livelihood patterns and a questionnaire was applied to learn how each group responded to drought. Data were analysed within the three livelihood types that were identified and described at local level as cattle-based, crop-based and non-farm based. We found that factors that aggravated the effects of drought are specific to the different household types and their responses were also specific to that particular household type. Disaggregation of the livelihood types revealed within and between type relations and interactions that are important to people in order to cope. For example, even though cropping is an important activity across the three livelihood types, specifically in cattle and crop-based types, the non-farm type becomes important in restocking inputs after a serious drought through cross-border trading. Livestock and cross-border trading are important coping strategies for all three livelihood types, with the cattle-based trading cattle, the crop-based trading goats and poultry and the non-farm based linking with markets for trading livestock, drugs and restocked inputs for the cattle-based and crop-based groups. These linkages among livelihood types are important factors in reducing vulnerability to change that only become visible as a result of this disaggregation. We conclude that additional policies of enhancing the resilience of local food systems by stimulating across-border livestock trading and formal market set-up and enhancing systems of adaptation that are already in existence (e.g., crop production in the Banyeni) can add value to the success of transfrontier conservation areas in southern Africa.